Core features of positive mental health in adolescents and their protective role against psychopathology - Desiree Y. Phua; Chermaine S. M. Chew (Scientific Reports)
Abstract Mental health is more than the absence of mental illnesses. However, while we acknowledge the importance of positive mental health, there is a lack of comprehensive understanding about positive mental health in adolescents and how it protects against psychopathology. This study seeks to understand adolescent positive mental health as a complex system by estimating the networks of components associated with positive mental health and their relationships to indicators of negative mental health. We analyzed data from 1909 adolescents aged 16–19 in Singapore using regular Gaussian Graphic models and Bayesian Directed Acyclic Graphs. Here we report positive self-image as a central upstream node with significant downstream effects on various aspects of well-being. Conversely, positive affect, social skills, perseverance and poor stress management are identified as downstream nodes with limited influence on other components. Our findings highlight the complex interplay between different dimensions of adolescent mental health and underscore the importance of positive self-image as a critical determinant of overall well-being. These results provide valuable insights for designing targeted interventions to enhance positive self-image to promote positive mental health and mitigate the risk of adverse outcomes among adolescents.